Nasalance Scores for Normal Speakers of American English Obtained by the Nasometer II Using the MacKay-Kummer SNAP-R Test. (June 2022) - Alfwaress, Firas; Kummer, Ann W.; Weinrich, Barbara
Objective: To establish nasalance score norms for adolescent and young adult native speakers of American English and also determine age-group and gender differences using the Simplified Nasometric Assessment Procedures (SNAP) Test-R and Nasometer II. Design: Prospective study using a randomly selected sample of participants. Setting: Greater Cincinnati area and Miami University of Ohio. Participants: Participants had a history of normal speech and language development and no history of speech therapy. Participants in the adolescent group were recruited from schools in West Clermont and Hamilton County, whereas the young adults were recruited from Miami University of Ohio. The participants of both groups were residents of Cincinnati, Ohio or Oxford, Ohio and spoke midland American English dialect. Outcome Measures: Mean nasalance scores for the SNAP Test-R. Results: Normative nasalance scores were obtained for the Syllable Repetition/Prolonged Sounds, Picture-Cued, and Paragraph subtests. Results showed statistically significant nasalance score differences between adolescents and young adults in the Syllable Repetition, Picture-Cued, and Paragraph subtests, and between males and females in the Syllable Repetition and the Sound-Prolonged subtests. A significant univariate effect was found for the syllables and sentences containing nasal consonants and high vowels compared to syllables and sentences containing oral consonants and low vowels. Across all the SNAP Test-R subtests, the females' nasalance scores were higher than the males. A significant univariate effect was also found across nasal syllables, and high vowels such that the females' nasalance scores were higher than the males. Tables of normative data are provided that may be useful for clinical purposes. Conclusion: Norms obtained demonstrated nasalance score differences according to age and gender, particularly in the Syllable Repetition/Prolonged Sound subtest. These differences were discussed in light of potential reasons for their existence and implications for understanding velopharyngeal function. In addition, nasalance scores are affected by the vowel type and place of articulation of the consonant. These facts should be considered when nasometry is used clinically and for research purposes.